IMPLEMENTASI JIT PADA TAHAP SERAH DAN TERIMA KOMPONEN RING PISTON ENGINE DI PT. TMMI - Yani Koerniawan; Suhermanto Suhermanto; Anwar Hilman (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2022)
Through the background handover stage and receive the piston engine ring component conducted by PT. Toyota Manufacturing Motor Indonesia (TMMI) there are wasteful activities or do not have added value. Then the part of the way to eliminate waste in the handover activity and accept the component is by just in time (JIT), then later there will be eliminated stages. Through this research has the aim to analyze the implementation of Just In Time and the influence of the implementation itself on these components. The method used in this study is Root Cause Analysis (RCA), with the aim of eliminating wasteful activities into just in time activities. Then the result of this study is the identification of the existence of 3 roots that cause the problem of the wasteful activity. Just in time implementation can eliminate activities which initially had 9 process activities for handover and accept it into 4 process activities. The inspection section does not require back to carry out handover activities and accept the user of the goods. So that time will be more efficient than 33 minutes to 16 minutes by one time the handover activity and receive the component. Conclusion from handover and receive directly from the supplier of the production line (place of the user). Then causes the component does not require back to be stored in a transit warehouse, in the end the transit warehouse will disappear.